INTERAKSI DAN KETERGANTUNGAN MASYARAKAT SEKITAR TERHADAP KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) GUNUNG BROMO - Rezky Lasekti Wicaksono; Rissa Rahmadwiati; Dwi Apriyanto (Forestry Study Program University Of Mataram, 2020)
Mount Bromo Special Purpose Forest Areas (KHDTK) is expected to be able to fully manage Sebelas Maret University by involving stakeholders, including those related to the communities around the forest. This research is intended to understand the form of interaction and the level of comparison of people to forests. Mixed methods, namely qualitative and quantitative descriptive analysis used in this study to answer more complete research objectives. Mount Bromo KHdTK is by utilizing forests directly in the form of arable land (agroforestry patterns), energy (firewood), animal feed, air, and pine resin. Furthermore, the level of community participation in the forest is divided into three groups, namely low, medium, and high, with 49%, 38%, and 13%, respectively. Mount Bromo KHdTK continues to approve the community around the forest because they are the main party and first receive negative impacts from unsupported forest area management.